Ionomidotis mesophila (Ascomycota, Cordieritidaceae), a new species from tropical cloud forest in Mexico - Sánchez Flores, Marcos; Martínez-Pineda, Michelle; Raymundo, Tania (Instituto de Ecología, A.C., 2021)
Background and Aims: The ascomycete genus Ionomidotis is characterized by solitary to caespitose ascomata, discoid to spathulate, olive to black, that release purple, violet, olive or green pigments in KOH. It is found in the order Helotiales of the class Leotimycetes. The present study aims to describe Ionomidotis mesophila as a new species for science.Methods: The specimens were collected in 2017 and 2019 in the municipality of Honey, Puebla, Mexico. The samples were studied and determined according to traditional techniques in mycology and were deposited in the fungus collection of the herbarium of the Escuela Nacional de Ciencias Biológicas of the Instituto Politécnico Nacional.Key results: The genus Ionomidotis is registered for the first time from Mexico and I. mesophila is decribed as a new species characterized by spathulate to cupuliform apothecia with a wavy, grayish brown margin that, in the presence of 5% KOH, releases fresh green to olive-brown pigments; paraphyses with rounded to globose apices and ellipsoid ascospores. It grows on recently fallen Quercus in cloud forest.Conclusions: Ionomidotis mesophila is a new species for cloud forest inventories in Mexico. It is necessary to accelerate efforts to inventory and describe the fungal diversity of tropical cloud forest, actually defined as an ecosystem in danger of extintion in the country.